2023
DOI: 10.1002/advs.202300670
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stimulations with Bioengineered Extracellular Matrix‐Mimicking Hydrogels for Mechano Cell Reprogramming and Therapy

Abstract: Cells interact with their surrounding environment through a combination of static and dynamic mechanical signals that vary over stimulus types, intensity, space, and time. Compared to static mechanical signals such as stiffness, porosity, and topography, the current understanding on the effects of dynamic mechanical stimulations on cells remains limited, attributing to a lack of access to devices, the complexity of experimental set-up, and data interpretation. Yet, in the pursuit of emerging translational appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 364 publications
0
6
0
Order By: Relevance
“…In contrast, TGF-b pathways enhance NF-kB activation, facilitating muscle growth and increasing cellular proliferation. 32,33 To assess the impact of the mechanical stimulation on cells during the blade-casting process, we measured gene expression 1 day after cell culture, which is related to mechanical stimulation (Figure 2B). The results indicated that the addition of blade casting to the bioprinting process significantly increased gene expression in the blade-casted cell construct compared with that in cell constructs fabricated solely through bioprinting, indicating that the mechanical stress applied through blade casting may play an important role in organizing the cytoskeleton, aligning cells, and facilitating muscle development.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, TGF-b pathways enhance NF-kB activation, facilitating muscle growth and increasing cellular proliferation. 32,33 To assess the impact of the mechanical stimulation on cells during the blade-casting process, we measured gene expression 1 day after cell culture, which is related to mechanical stimulation (Figure 2B). The results indicated that the addition of blade casting to the bioprinting process significantly increased gene expression in the blade-casted cell construct compared with that in cell constructs fabricated solely through bioprinting, indicating that the mechanical stress applied through blade casting may play an important role in organizing the cytoskeleton, aligning cells, and facilitating muscle development.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure A shows that cells within a collagen bioink experience mechanical stimulation during the blade casting process, wherein mechanical forces are transmitted via the extracellular matrix (ECM) and neighboring cells. This stimulation is detected by integrin receptors and mechanosensitive ion channels such as transient receptor protein ion channels and Piezo ion channels, activating focal adhesion kinase (FAK) and initiating various signaling pathways, including RhoA/Rock, Wnt/b-catenin, MAPK, TGF-b, and Pi3K. The activation of these pathways regulates cellular responses, such as proliferation, cytoskeleton formation, and gene expression. The RhoA/Rock pathway promotes actin stress fiber formation, and the activated Wnt/b-catenin pathway stimulates nuclear activity and gene expression. In contrast, TGF-b pathways enhance NF-kB activation, facilitating muscle growth and increasing cellular proliferation. , …”
Section: Resultsmentioning
confidence: 99%
“…Since cells in vivo are surrounded by 3D ECM, whose architecture is influenced and dynamically changed by the cells in an inter-dependent fashion [49], we next aimed at developing an analogous system allowing for a similar spatiotemporal control of cell and ECM orientation in 3D. In particular, knowing that uniaxially constrained static tissues can provide stiffness cues aligning cells and ECM [29,30,42,50], we leveraged the crosslinking properties of GelMA to develop uniaxially constrained and temporally dynamic 3D tissues.…”
Section: Generation Of Stiffness Macropatterns In 3d Cell Culturesmentioning
confidence: 99%
“…Current research suggests that immoderate stretching could act as a significant stimulant for myocardial injury and continuing activation of myofibroblasts, ultimately leading to the development of fibrosis. [93][94][95] McCain et al imitated mechanical overexertion by circularly stretching designed layered cardiovascular tissues on an elastic chip. 96 Periodic stretching was found to activate indicators of abnormal heart hypertrophy, change myocyte morphology and filament orientation, modify calcium transient, and diminish stress production.…”
Section: Dynamic Stretchingmentioning
confidence: 99%